The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1601-0825.2004.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

The validation of self‐reported smoking status by analysing cotinine levels in stimulated and unstimulated saliva, serum and urine

Abstract: Cotinine, whatever the collection method and analysed by EIA kits, shows good differentiation between smokers and non-smokers. Salivary samples have the advantage of being non-invasive, although collection methodology is important, as cotinine levels may vary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 23 publications
7
80
1
Order By: Relevance
“…Accordingly, future studies on the biological bases of ethanol and nicotine interactions are necessary and the use of other strains and species may provide valuable data. Though nicotine concentration may seem high in the drinking solution, nicotine absorption from the buccal cavity yields cotinine plasma levels (Klein et al, 2003(Klein et al, , 2004Sparks and Pauly, 1999) comparable to those found in adolescent smokers (Binnie et al, 2004;Caraballo et al, 2004;Wood et al, 2004). As for ethanol, according to previous studies in adolescent rodents, even the moderate doses used in the present study result in blood levels well above the legal driving limit (Silveri and Spear, 2000).…”
Section: Methodological Issuessupporting
confidence: 73%
“…Accordingly, future studies on the biological bases of ethanol and nicotine interactions are necessary and the use of other strains and species may provide valuable data. Though nicotine concentration may seem high in the drinking solution, nicotine absorption from the buccal cavity yields cotinine plasma levels (Klein et al, 2003(Klein et al, , 2004Sparks and Pauly, 1999) comparable to those found in adolescent smokers (Binnie et al, 2004;Caraballo et al, 2004;Wood et al, 2004). As for ethanol, according to previous studies in adolescent rodents, even the moderate doses used in the present study result in blood levels well above the legal driving limit (Silveri and Spear, 2000).…”
Section: Methodological Issuessupporting
confidence: 73%
“…First, cigarette smoking and cessation-related measures were self-reported without validation by biochemical testing, and might be subject to social desirability bias. However, selfreported smoking status correlates with serum cotinine levels (10). Second, because NHIS does not include institutionalized populations and persons in the military, results are not generalizable to these groups.…”
Section: Characteristicmentioning
confidence: 75%
“…Other methods that could more accurately estimate smoking exposure are expired carbon monoxide levels and cotinine measurements in body fluids such as saliva, serum and urine (Dolcini et al 2003). The relationships between self-reported smoking data and cotinine levels in some body fluids have been shown to be highly correlated (Binnie et al 2004). …”
Section: Limitations Of the Studymentioning
confidence: 99%